2008
DOI: 10.1021/bm800751e
|View full text |Cite
|
Sign up to set email alerts
|

Net Charge Affects Morphology and Visual Properties of Ovalbumin Aggregates

Abstract: The effect of ovalbumin net charge on aggregate morphology and visual properties was investigated using chromatography, electrophoresis, electron microscopy, and turbidity measurements. A range of differently charged ovalbumin variants (net charge ranging from -1 to -26 at pH 7) was produced using chemical engineering. With increasing net charge, the degree of branching and flexibility of the aggregates decreased. The turbidity of the solutions reflected the aggregate morphology that was observed with transmis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
34
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(35 citation statements)
references
References 32 publications
1
34
0
Order By: Relevance
“…In the absence of salt, OVA conformation exhibits a nearly reversible two-state heat-induced transition with a midpoint temperature of 76°C and reaches an almost completely unfolded state with a significant degree of secondary structure at 80°C (23). In the presence of salt, OVA undergoes irreversible heat denaturation with the formation of semiflexible fibrillar types of aggregates (23)(24)(25)(26)(27)(28). Unlike the other serpins, the aggregation mechanism of OVA has been suggested to resemble that of amyloid fibril formation (25,27).…”
mentioning
confidence: 99%
“…In the absence of salt, OVA conformation exhibits a nearly reversible two-state heat-induced transition with a midpoint temperature of 76°C and reaches an almost completely unfolded state with a significant degree of secondary structure at 80°C (23). In the presence of salt, OVA undergoes irreversible heat denaturation with the formation of semiflexible fibrillar types of aggregates (23)(24)(25)(26)(27)(28). Unlike the other serpins, the aggregation mechanism of OVA has been suggested to resemble that of amyloid fibril formation (25,27).…”
mentioning
confidence: 99%
“…As a rule, environmental conditions that promote exposure of local poles of high net charges and/or β-sheet structure also promotes head-to-tail aggregation, hence fibrillation. Hence, various studies have reported that globular proteins such as ovalbumin (Weijers et al 2008), β-LG (Bolder et al 2007;Durand et al 2002;Ikeda and Morris 2002;Jung et al 2008), BSA (Holm et al 2007) or partially hydrolysed α-LA (Otte et al 2005) can yield fibrils on (even moderate) heat treatment at low ionic strength values and at pH generally~7.0 or~2.0 depending on proteins. Elongated particles of β-LG can further be produced in water at pH~7.0 and ≤50 mmol.L −1 NaCl (Alting et al 2004;Pouzot et al 2005).…”
Section: Possible Methods To Modify the Size Of The Heat-induced Wheymentioning
confidence: 99%
“…Cryo-EM investigation of aggregates formed from ovalbumin which had been succinylated to various degrees provided further evidence that net charge dominantly determines aggregate morphology (Weijers et al, 2008). The propensity of proteins to aggregate, or rate of aggregation, has been shown to vary as a function of protein conformational stability (Chiti et al, 2000;Hurle et al, 1994;Kelly, 1998;Quintas et al, 1997;Ramirez-Alvarado et al, 2000;Siepen & Westhead, 2002), rate of unfolding (Broersen et al, 2007a), net charge (Calamai et al, 2003;DuBay et al, 2004), and secondary structure propensity (Fernandez-Escamilla et al, 2004).…”
Section: Aggregation and Gelationmentioning
confidence: 98%
“…These hypotheses have been substantiated by a range of observations which involved charge introduction, removal or reversal through succinylation and methylation reactions (Broersen et al, 2007a;Weijers et al, 2008). The reactions of succinylation and acetylation both lead to blockage of the reactive amino groups of proteins with an acyl residue and are hence collectively termed acylation reactions.…”
Section: Charge Modification By Methylation and Succinylationmentioning
confidence: 99%
See 1 more Smart Citation